The Shawshank redemption Castle Rock Entertainment presents a Frank Darabont film ; screenplay, Frank Darabont ; producer, Niki Marvin ; director, Frank Darabont. - Robbins, Tim, 1958-; Freeman, Morgan; Gunton, Bob; Sadler, William, 1950-; Brown, Clancy; Bellows, Gil; Whitmore, James, 1921-2009; Darabont, Frank; King, Stephen, 1947- (Columbia TriStar Home Video, 1995)
Two convicts, one white and one black, never give up the dream of freedom, and together they turn hope and friendship into an uplifting bond no prison can ever take away.
Based on the short novel "Rita Hayworth and Shawshank Redemption" by Stephen King.
"This film has been modified from its original version. It has been formatted to fit your television."
Originally produced as motion picture in 1994.
Hi-fi Dolby surround stereo.
Rated R.
Keywords: Prisons -- Drama.; Feature films.; Video recordings for the hearing impaired.